A genetic regulatory see-saw of biofilm and virulence in MRSA pathogenesis - Patel, Hardi; Rawat, Seema (Frontiers in Microbiology, 2023)
Staphylococcus aureus is one of the most common opportunistic human pathogens causing several infectious diseases. Ever since the emergence of the first Methicillin resistant Staphylococcus aureus (MRSA) strain decades back, the organism has been a major cause of hospital acquired infections (HA-MRSA). Spread of this pathogen across the community, led to the emergence of a more virulent subtype of the strain i.e., CA-MRSA. Hence WHO has declared Staphylococcus aureus as a high priority pathogen. MRSA pathogenesis is remarkable because of the ability of this ‘superbug’ to form robust biofilm both in vivo & in vitro by formation of polysaccharide intercellular adhesin (PIA), extracellular DNA (eDNA), wall teichoic acids (WTAs) and capsule (CP) which are major components that impart stability to a biofilm. On the other hand, secretion of a diverse array of virulence factors like hemolysins, leukotoxins, enterotoxins, Protein A etc. regulated by agr and sae two component systems (TCS) aids in combating host immune response. The up and down regulation of adhesion genes involved in biofilm formation and genes responsible for synthesizing virulence factors during different stages of infection acts as a genetic regulatory see-saw in pathogenesis of MRSA. This review provides an insight into the evolution and pathogenesis of MRSA infections with a focus on genetic regulation of biofilm formation and virulence factors secretion.